Erratum to: In canine acute diarrhoea with no identifiable cause, does daily oral probiotic improve the clinical outcomes? - Oi Ping Tong, Jacqueline (Veterinary Evidence, 2020)
The original version of the article has been corrected, please see the full text for details of the correction.